Peningkatan Kesadaran Lingkungan Masyarakat Desa Cidadap Kabupaten Subang Melalui Pembuatan Biopori: Pengabdian - Sulaiman Miftahul Ghina; Gilang Hari Mukti; Jennie Anatasha Wijaya; Alisa Amalia; Jilli Zildjian Richadt; M. Rio Syahputra; Susilawati; Evi Alia Elfarina; Muhammad Rizky Fauzi; Titin Kartini (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aims to increase environmental awareness in the Cidadap Village community through the creation of biopores. This activity is part of the KKNM program, which includes education, health, and sustainable environmental management. Through outreach and education by students, the community is educated about the importance of biopores in maintaining soil quality and preventing flooding. This activity is also related to the stunting prevention program and addresses other social issues such as bullying in local schools. The participatory method used directly involves the community, increasing their involvement and awareness of environmental issues. The results show an increase in community knowledge about environmental management and the positive impact of biopores on soil health. It is hoped that this activity can become a model for other villages to increase environmental awareness and sustainable natural resource management.